2022
DOI: 10.1016/j.psychres.2022.114428
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of US undergraduate and graduate students before and during the COVID-19 pandemic: Differences across sociodemographic groups

Abstract: The purposes of this study were to assess differences between sociodemographic groups in student mental health before and during the COVID-19 pandemic, to investigate whether the pandemic disproportionately affected certain groups, and to examine between-group differences in pandemic-related stressors. Data from Minnesota undergraduate and graduate students who completed an online survey in 2020 ( N = 2,067) were compared to data collected from students in 2018 (N = 3,627). The survey as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…A comparative study revealed severe stress management imbalance during the pandemic, compared to 2018 [ 15 ]. Similarly to other studies, it was noticed that female students and students with disabilities and different sexual orientation respondents faced significant difficulties and their mental health was aggravated during the pandemic [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study revealed severe stress management imbalance during the pandemic, compared to 2018 [ 15 ]. Similarly to other studies, it was noticed that female students and students with disabilities and different sexual orientation respondents faced significant difficulties and their mental health was aggravated during the pandemic [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies observed that sexual minorities, in general, presented worse mental health than the heterosexual population during lockdown ( Duarte & Pereira, 2021 ; Liu et al, 2022 ). In our study, we focused only on women and it seems that the differences are less clear, since no statistically significant differences were observed.…”
Section: Discussionmentioning
confidence: 94%
“…2) Family income: students' annual net family income per capita has a significant impact on students' mental health [9]. In this paper, students' annual net family income per capita was extracted into five clusters: absolute poverty, which means income is less than 627¥; relative poverty, which means income is between 627¥ and 865¥; low income, which means income is between 865¥ and 1205¥; middle income, which means income is between 1205¥ and 10000¥; high income, which means income is above 10000¥.…”
Section: Feature Extraction Of Students' Status Datamentioning
confidence: 99%